The influence of flywheel micro vibration on space camera and vibration suppression. (1st February 2018) - Li, Lin; Tan, Luyang; Kong, Lin; Wang, Dong; Yang, Hongbo
Highlights: Measuring method of micro vibration produced by flywheel is proposed. Micro vibration produced by flywheel should be strictly controlled during imaging. Micro vibration isolator is designed according to the effect of micro vibration. Abstract: Studied the impact of flywheel micro vibration on a high resolution optical satellite that space-borne integrated. By testing the flywheel micro vibration with six-component test bench, the flywheel disturbance data is acquired. The finite element model of the satellite was established and the unit force/torque were applied at the flywheel mounting position to obtain the micro vibration data of the camera. Integrated analysis of the data of the two parts showed that the influence of flywheel micro vibration on the camera is mainly concentrated around 60–80 Hz and 170–230 Hz, the largest angular displacement of the secondary mirror along the optical axis direction is 0.04″ and the maximum angular displacement vertical to optical axis is 0.032″. After the design and installation of vibration isolator, the maximum angular displacement of the secondary mirror is 0.011″, the decay rate of root mean square value of the angular displacement is more than 50% and the maximum is 96.78%. The whole satellite was suspended to simulate the boundary condition on orbit; the imaging experiment results show that the image motion caused by the flywheel micro vibrationis less than 0.1 pixel after installing the vibration isolator.